Pujakesuma Organizational Communication In Langkat Regency For Regional Development Optimization (Pena Cendekia Insani, 2022)
The purpose of this article is to learn how the Pujakesuma organization communicates in order to optimize regional development. The descriptive qualitative method was used in this study. The Langkat Regency Family Association is the subject of this study's research. The findings revealed that the Pujakesuma organization's communication in Langkat Regency was effective in optimizing regional development. One of the efforts to assist the Langkat district government in optimizing regional development is the establishment of good relations with the local government. The Pujakesuma Family Association agreed to continue supporting the Langkat Regency regional development program. Infrastructure, equality, and even human resource development are all examples. Pujakesuma, as a social organization, also intends to establish a tahfiz school in the Langkat district in the future to produce more qualified human resources.